Model of Basic Locomotor Movement with Balance for 1st Grade Elementary School Children - Bonggo Pribadi; Yasep Setiakarnawijaya; Mansur Jauhari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to obtain information in the process of implementing basic locomotor movement learning with balance, creating and transmitting the learning process with basic locomotor movement models with balance for elementary school children in grade I to obtain empirical data about the effectiveness and efficiency and interest of children from the motion learning process. basic locomotor with balance for elementary school children in class I and created a learning model book for teachers as a guide for teaching basic locomotor movements with balance for elementary school children. This will increase effectiveness and efficiency as well as increase children's motivation to learn basic locomotor movements with balance. This research was conducted at SDN Semanan 14 Petang, West Jakarta, with 32 children as research objects. This study uses the ADDIE learning development model, which in this model starts at the stages of Analysis, Design, Development, Implementation, and Evaluation. From the results obtained, the basic locomotor motion learning model with this balance turned out to be very effective to be applied in learning. From the results obtained, the basic locomotor motion learning model with this balance turned out to be very effective when applied in learning. This can be seen from the increase in pre-test and post-test by using the paired sample test on the SPSS 25.0 T-Test. The difference in significance on T-count is shown as -98.097 df = 31, p-value = 0.001 <0.05 ; With this, there appears to be a significant increase in the results of the assessment of children's skills at SDN Semanan 14 Petang Class I.